2022
DOI: 10.1111/bph.15803
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating islet‐derived protein 3 gamma (Reg3g) ameliorates tacrolimus‐induced pancreatic β‐cell dysfunction in mice by restoring mitochondrial function

Abstract: Background and Purpose Tacrolimus a first‐line medication used after transplantation can induce β‐cell dysfunction, causing new‐onset diabetes mellitus (NODM). Regenerating islet‐derived protein 3 gamma (Reg3g), a member of the pancreatic regenerative gene family, has been reported to improve type 1 diabetes by promoting β‐cell regeneration. We aim to investigate the role of Reg3g in reversing tacrolimus‐induced β‐cell dysfunction and NODM in mice. Experimental Approach Circulating REG3A (the human homologue o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…One study showed that exogenous delivery of REG3G contributes to the progression of chronic pancreatitis towards neoplasia [98]. At the same time, another study showed that it ameliorates pancreatic β-cell dysfunction in mice [99]. Previous publications demonstrated that Cre recombinase activity is increased in female mice compared to male mice [37,100] and that tamoxifen treatment may have a different effect on female and male mice [101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that exogenous delivery of REG3G contributes to the progression of chronic pancreatitis towards neoplasia [98]. At the same time, another study showed that it ameliorates pancreatic β-cell dysfunction in mice [99]. Previous publications demonstrated that Cre recombinase activity is increased in female mice compared to male mice [37,100] and that tamoxifen treatment may have a different effect on female and male mice [101][102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, as a heterotrimeric Ser/Thr kinase, is stimulated by variations in the cellular ratio of AMP to ATP, which acts as an energy sensor to regulate oxidative stress and energy homeostasis, promoting mitochondrial functionality and repressing degenerative nerve diseases [ 17 , 18 ]. The anti-inflammatory effect of AMPK activation has been revealed, which was achieved by lowering the levels of neuron-mediated inflammatory cytokines [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The culture system in the Transwell was consistent with that on the well plates. Additionally, tacrolimus (HY-13756, MedChemExpress, Monmouth Junction, NJ, USA) was dissolved in dimethyl sulfoxide (DMSO, Sigma-Aldrich, Merck, Darmstadt, Germany), and its concentration was adjusted to 800 ng/mL in DMEM complete medium [ 28 ]. Stattic, a potent STAT3 inhibitor, (HY-13818, MedChemExpress), was also dissolved in DMSO, and its concentration was adjusted to 100 μm in the DMEM complete medium.…”
Section: Methodsmentioning
confidence: 99%